Improvement of the Seed Metering Device of Power Tiller Operated Zero Till Drill (Progressive Agriculture, 2014)
This study was carried out in wheat research center, BARI under financial assistance of CIMMYT for the improvement of seed metering device of a power tiller operated zero till drill planter. Fluted roller type seed metering device was replaced by the inclined plate type seed metering device. Field experiments revealed that field efficiency was 80.19% and seed damage was completely absent in the improved metering device. Further cost analysis showed saving of 280 Taka ha-1 planting cost, which proves success of the improvement.DOI: http://dx.doi.org/10.3329/pa.v24i1-2.19173 Progress. Agric. 24(1&2): 203 - 210, 2013